Contribution of Peripheral Chemoreceptors to Exercise Intolerance in Heart Failure - Kulej-Lyko, Katarzyna; Niewinski, Piotr; Tubek, Stanislaw; Ponikowski, Piotr (Frontiers in Physiology, 2022)
Peripheral chemoreceptors (PChRs), because of their strategic localization at the bifurcation of the common carotid artery and along the aortic arch, play an important protective role against hypoxia. Stimulation of PChRs evokes hyperventilation and hypertension to maintain adequate oxygenation of critical organs. A relationship between increased sensitivity of PChRs (hyperreflexia) and exercise intolerance (ExIn) in patients with heart failure (HF) has been previously reported. Moreover, some studies employing an acute blockade of PChRs (e.g., using oxygen or opioids) demonstrated improvement in exercise capacity, suggesting that hypertonicity is also involved in the development of ExIn in HF. Nonetheless, the precise mechanisms linking dysfunctional PChRs to ExIn remain unclear. From the clinical perspective, there are two main factors limiting exercise capacity in HF patients: subjective perception of dyspnoea and muscle fatigue. Both have many determinants that might be influenced by abnormal signalling from PChRs, including: exertional hyperventilation, oscillatory ventilation, ergoreceptor oversensitivity, and augmented sympathetic tone. The latter results in reduced muscle perfusion and altered muscle structure. In this review, we intend to present the milieu of abnormalities tied to malfunctioning PChRs and discuss their role in the complex relationships leading, ultimately, to ExIn.